Peran Perbankan Syariah Terhadap Ketahanan Keluarga di Era Pandemi Covid-19 - Alfian (Hukum Keluarga Islam IAIN LANGSA, 2022)
The family becomes important in the defense and protection of its members. For this reason, it is necessary to ensure that every family has good capital in order to be able to face various difficult and challenging life situations. This study aims to determine family resilience during a pandemic, as well as factors that support and hinder the resilience of the family by using family demographic groups, namely family type, parental occupation, and residential area. The approach used in this research is descriptive qualitative used with research subjects totaling 100 people. The results of the study show that the economic resilience of the family during the Covid-19 pandemic has decreased, especially in terms of income and ability to meet family needs. However, from the aspect of housing ownership, financing for children's education, and family financial security, the economic resilience of the family in Indonesia can be considered quite good. This study recommends the need for a fairly good family financial management strategy. Family resilience in this study was measured using the Walsh Family Resilience Questionnaire developed by Walsh (2012) and analyzed using descriptive statistical analysis techniques.